IMPROVING LEARNERS’ ENGLISH THROUGH THE USE OF PICTURES IN LANGUAGE CLASSROOM - Mulyadi Mulyadi (ELTE Journal (English Languange Teaching and Education), 2014)
Abstract  There are many ways that can be done by a teacher or lecturer in motivating and helping his students to understand and communicate in English in the classroom. One of them is by using teaching aids, pictures. "Pictures" are not only able to make the students interested in what is being learned, helping students understand the lessons easily and involve them actively in the learning process but also can provide a visual clue for them to respond. However, before the "Pictures" are used in the teaching of English in the classroom the teacher must prepare well. Teachers should pay attention to whether the "Pictures" are easy to set up and attractive in order to be used effectively and meaningfully.  Key words: teaching aids, pictures, communication